Spirit, Spoken Word, and the Search for Common Ground: Amanda Gorman as Contemplative Preacher (Homiletic, 2024)
Amid profound political fragmentation, the poet and activist Amanda Gorman demonstrates the power of the spoken word to build bridges toward greater justice and wholeness for all people. Drawing on select theologies of the Spirit and especially Howard Thurman’s notion of common ground, this article considers Gorman’s inaugural poem “The Hill We Climb” as an act of pneumatological or Spirit-inspired contemplative proclamation that fosters community in a time of division. Specific attention is given to how preachers and other communicators might learn from Amanda Gorman’s example to contribute toward social and spiritual healing in our beautiful yet broken world today.